Performance of soybean grown in succession to black oat and wheat - Balbinot Junior, Alvadi Antonio; Santos, Julio Cezar Franchini dos; Debiasi, Henrique; Coelho, Antônio Eduardo; Sapucay, Moryb Jorge Lima da Costa; Bratti, Felipe; Locatelli, Jorge Luiz (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the influence of isolated or combined roots and straw of black oat and wheat, as previous crops in autumn/winter, on the performance of soybean in succession. The experiment was carried out in the 2017/2018 and 2018/2019 crop seasons in a randomized complete block design, with four replicates. The following seven treatments were applied in the autumn/winter of 2017 and 2018, before soybean planting: fallow; straw of black oat or wheat, distributed on plots kept under fallow during autumn/winter, without roots; plots only with roots of black oat or wheat, without straw; and plots with straw and roots of black oat or wheat. Soybean crop performance was estimated using the following variables: plant density, leaf area index, soil plant analysis development (SPAD) index, shoot dry matter, grain yield, and yield components. In comparison with fallow, the cultivation of black oat or wheat, as previous crops during the autumn/winter, increases soybean grain yield. The impact of the roots of black oat or wheat on soybean yield is similar to that of straw. Soybean agronomic performance is improved in the combined presence of roots and straw of black oat or wheat.